KEPEMIMPINAN PENDIDIKAN ISLAM (Analisis Makna Kata "Khalifah" dalam Al Qur’an) - M. Yusuf Agung Subekti; Mochamad Nurcholiq (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
To interpret thematically is to determine the topic. The topic of this discussion is the meaning of "caliph" and its relationship to the theme of educational leadership. The word caliph in the singular is repeated only 2 times, the jamaic form, with the word Ø®Ù„Ø§ Ø¦Ù repeated 4 times and the word Ø®Ù„ÙØ§Ø¡ is repeated 3 times. The meaning of the khalifah contained in the Qur'an is a description of the role and function of leadership. The description of "khalifah" in accordance with the concept that is synchronized with Zikr-Pikr and Mikr, which in the meaning of the word Zikr is remember or conscious, with zikr in every activity will always be aware and able to control themselves, its means using the mind to always make new innovations and always be creative, and then Pikr is the tought of Mikr in the form of ideas or innovations and creations in the form of programs and their implementation.